Износостойкость детонационных покрытий системы FeAl2-Ti-Si при нагружении трением в условиях повышенных температур - Бабак, В. П.; Лисовой, Е. Н.; Мирненко, В. И.; Щепетов, В. В. (ООО «Компания «Индустриальные технологии», 2014)
Исследовано трение и износ детонационных композиционных покрытий FeAl2-Ti-Si в условиях высокотемпературного трения. Обоснован выбор композиции и ее оптимальный состав для напыления износостойких покрытий, нагруженных трением в условиях высоких температур. Отмечено, что положительное воздействие на структуру, свойства и качество многокомпонентных покрытий оказывают легирующие элементы при определенных концентрациях, а также технологические параметры напыления. Показано, что кремний и титан способствуют образованию сложнолегированных высокотемпературных соединений, обладающих повышенным сопротивлением износу. Максимальную микротвердость имеют покрытия FeAl2-Ti при содержании титана ~28%, при этом механические свойства материала повышаются путем дополнительного легировании кремнием~22% бора. В свою очередь, при расходах рабочих газов ацетилена-кислорода ~(22–27)г/л обеспечивается стабильность технологических параметров напыления, неизменность химического состава и постоянство свойств покрытий. При нагрузке 5,0 МПа, скорости скольжения 1,5 м/с и температуре до 650 °С покрытия системы FeAl2-Ti-Si проявляют устойчивую структурную приспосабливаемость, обеспечивающую минимизацию параметров трения и изнашивания. Металлографический анализ и профилографирование образцов свидетельствуют о том, что на поверхностях трения отсутствуют заметные повреждения, а отдельные очаги схватывания локализуются в тонкопленочных поверхностных слоях. Определены высокая адгезия, физико-механические характеристики и сопротивление износу покрытий в условиях повышенных температур, современными физико-химическими методами анализа изучены структура и свойства тонкопленочных поверхностных объектов. Установлено что, сочетание механических и физико-химических характеристик обеспечивает широкие возможности использования покрытий FeAl2-Ti-Si в условиях высокотемпературного износа. The investigation results of friction and wear of the developed detonation composite coatings FeAl2-Ti-Si under high-temperature friction conditions are presented. The choice of FeAl2-Ti-Si composition and its optimal content for spraying of wear-resistant coatings loaded with friction under high-temperature conditions are justified. It is noted that the alloying elements at definite concentrations and technological parameters of spraying have positive influence on structure, properties and quality assurance of multicomponent coatings. It is shown that the introduction of silicon and boron promote the formation of hard-alloy high-temperature compounds with increased wear resistance. The maximum microhardness corresponds to the Cr–Si coatings with ~28% titan content. Besides, the mechanical properties of the obtained material are improved by additional alloying of ~22% silicon. In turn, the coatings plating at working gas flow rate in a ratio for acetylene ~(20/25) l/min and oxygen ~(22/27) l/min provides the chemical composition and spraying process parameters permanence as well as constant properties of coatings. The obtained results show that for the coatings of FeAl2-Ti-Si system at loading 5.0 MPa, sliding speed 1.5 m/s and temperature up to 650 °С the stable performance of structural adaptability, which provides the friction and wear parameters minimization, is demonstrated. The metallographic analysis and strip chart recording of specimens indicate that the friction surfaces are characterized with the absence of visible defects; the separate cold-welded regions are located in thin-film surface layers. The composition, structure and tribological durability of coatings produced from the elements of resource base of the country were studied; their high adhesion, physical and mechanical characteristics and wear resistance under high-temperature conditions were defined. The thin-film surface structures pattern and properties were investigated with the help of modern physical and chemical methods of analysis. It was determined that the combination of mechanical, physical and chemical properties of the investigated coatings provides wide opportunities for their usage as effective materials under high-temperature wear conditions. According to the test results, the application of the investigated composite coatings for friction units efficiency improvement provides their operational reliability in accordance with requirements and opportunities that appear with the development of a new competitive material for wear-resistant coatings obtained with the help of detonation method.
Wear-resistant FeAl2-Ti-Si detonation spray coatings under friction loading at elevated temperatures
Keywords: детонационное покрытие; износостойкость; поверхностный слой; структурная приспосабливаемость; температура; detonation coating; wear resistance; surface layer; structural adaptability; temperature